2014
DOI: 10.1007/s10854-014-2096-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiwalled carbon nanotubes on the crystallization and dielectric properties of BP-PEN nanocomposites

Abstract: In this work, polymer-based nanocomposite films formed from biphenol poly(arylene ether nitrile) (BP-PEN) and multiwalled carbon nanotubes (MWCNTs) were successfully prepared by the solution casting method combined with continuous ultrasonic dispersion technology. The micromorphology, thermal, mechanical and dielectric properties of the nanocomposite films were investigated in detail. Non-isothermal crystallization behavior studies indicate that the presence of MWCNTs enhances the crystallization of BP-PEN in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…• , which is in accordance with previous reports 13 .In contrast, the diffraction pattern of the stretched specimens showed a sharper and stronger peak at about 2ɵ = 18 • . This indicated that some of the polymer crystal structures disappeared or reduced after hot stretch process and other crystal structures become more stable and perfect.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…• , which is in accordance with previous reports 13 .In contrast, the diffraction pattern of the stretched specimens showed a sharper and stronger peak at about 2ɵ = 18 • . This indicated that some of the polymer crystal structures disappeared or reduced after hot stretch process and other crystal structures become more stable and perfect.…”
Section: Resultssupporting
confidence: 93%
“…Polyarylene ether nitriles(PEN), as a special thermoplastic engineering material, possesses various outstanding properties, including excellent mechanical properties, high thermal stability, radiation resistance and chemical inertia nature, etc [9][10][11] . These characteristics make it a good candidate to be used in industrial, automotive and outer space fields encountered with high temperature or high radiation exposure [12][13][14] . Many studies have reported that MWCNTs can be well dispersed in the polymer matrix and act as a nucleation site for crystal polymer [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Scheme 1, the PEN copolymers with pendant carboxyl groups were synthesized via the nucleophilic aromatic substitution polymerization of 2, 6-dichlorobenzonitrile with different ratios of 4, 4-Bis(4-hydroxyphenyl)valeric acid and biphenol in the presence of K 2 CO 3 , according to the procedure described in the literature [9]. A series of PEN-COOH copolymers with different contents of carboxyl groups were obtained by varying the molar ratios of 4, 4-bis(4-hydroxyphenyl)valeric acid to biphenol.…”
Section: Methodsmentioning
confidence: 99%
“…Polyarylene ether nitrile (PEN) is a class of high performance engineering thermoplastics due to its outstanding mechanical properties, high thermal stability and excellent chemical resistance accompanying with good processibility and film-forming ability [7][8][9]. Moreover, chemical modifications of such polymer may lead to further innovative applications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these charming properties, CNTs have been widely adopted in substituting or replenishing traditional nanofillers to prepare composites with different functions. Zheng et al [94] prepared composite films by using 4,4 ′ -dihydroxybiphenyl-based PEN as the organic substrate and multiwalled carbon nanotubes (MWCNTs) as additives. The permittivity of the obtained mixture increases from 4.3 to 6.1 (1 kHz) with the content of MWCNT fillers increases from 0 wt% to 3 wt%, exhibiting little frequency dependence with the incorporation of MWCNTs.…”
Section: Metal Conductive Particles As Fillersmentioning
confidence: 99%